2007
DOI: 10.1128/jvi.02247-06
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Destruction of Focal Adhesions Revealed in a High-Throughput Western Blot Analysis of Cellular Protein Expression

Abstract: Human cytomegalovirus (HCMV) is a clinically important herpesvirus associated with severe disease following congenital infection and in immunocompromised individuals. As a herpesvirus, primary infection is accompanied by lifelong persistence during which the infection must be controlled by continuous host immune surveillance. HCMV has the largest genome of any characterized human virus (ϳ236 kb) and is predicted to encode on the order of 165 potential open reading frames (15). Systematic deletion of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 62 publications
7
41
0
Order By: Relevance
“…3B). Consistent with an earlier report (18), WT virus also substantially reduced cell surface staining with vinculin (Fig. 3A, Upper), a protein found at the intersection of actin bundles and membrane attachment sites (19).…”
supporting
confidence: 79%
“…3B). Consistent with an earlier report (18), WT virus also substantially reduced cell surface staining with vinculin (Fig. 3A, Upper), a protein found at the intersection of actin bundles and membrane attachment sites (19).…”
supporting
confidence: 79%
“…HCMV has been shown to increase hsp90 expression, and our data indicate that HCMV-mediated Nrf2 activation was abolished following treatment with CK2 inhibitors (Stanton et al, 2007). Altogether, these data would suggest that HCMV activates Nrf2 by manipulating the hsp90 and Keap1 interaction.…”
supporting
confidence: 58%
“…HCMV infection prevented the nuclear translocation of Nrf2 and failed to activate HO-1 expression. However, other investigations have shown that HO-1 expression is increased upon HCMV infection at the RNA or protein level when primary fibroblasts are used (Browne et al, 2001;Stanton et al, 2007). Therefore, the effect of HCMV infection on the Nrf2 pathway needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…HCMV strain Merlin (p5) (27) was utilized to generate BACs as described below. Infections were performed as described previously (78), and viruses were titrated in triplicate by plaque assay for 14 days on HFFFs using a 1% Avicel overlay (79). Cultures that exhibited small plaques at 14 days PT were incubated for a further 14 days and recounted.…”
Section: Methodsmentioning
confidence: 99%